Antiradical activity of novel 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives - A. A. Safonov; I. S. Nosulenko (Zaporozhye State Medical University, 2021)
The process of studying free radicals began in the middle of the last century (the free radical theory of aging in 1956). Multiple studies have revealed the effect of free radicals on the cells of the body and the development of various diseases, such as diabetes, autoimmune diseases, diseases of the nervous system, and others. As a result, the term antioxidant has emerged, compounds that reduce and prevent the effects of free radicals. Most of the newly synthesized substances are studied for their antiradical properties. 1,2,4-Triazole derivatives are no exception, which has already proven themselves as biologically active compounds. The aim of this work was the investigation antiradical activity among 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives. Materials and methods. Previously synthesized 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives were used as test compounds. The research of antiradical activity was based on the interaction between 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives and 2,2-diphenyl-1-picrylhydrazyl (DPPH) in vitro. DPPH is a stable free radical. The color of its alcoholic solutions were intense purple (λmax = 517 nm). When DPPH interacted with compounds that were capable of scavenging free radicals, it produced products. These products are yellow in color and do not absorb light of the aforementioned wavelength. The study was carried out according to the method. Results. The antiradical activity of 10 new 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives was studied. Most of the test compounds show antiradical activity against DPPH. Compound 1 was the most active at a concentration of 1 × 10-3 M and the antiradical effect was close to ascorbic acid. Conclusions. The most active compound is 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol, which in a concentration of 1 × 10-3 M has an antiradical effect in 88.89 %. When reducing the concentration to 1 × 10-4 M, also reduces the antiradical activity to 53.78 %. Some conclusions are drawn regarding the "structure - effect" dependence between 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives: - the introduction of 4-fluorobenzylidene radical (compound 2) into the 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol molecule results in a slight decrease in activity; - the introduction of 2-hydroxybenzylidene radical (compound 3) into initial molecule results a high antiradical effect, which hardly changes with decreasing concentration; - transformation to 2-((5-(thiophen-2-ylmethyl)-4-((R)amino)-4H-1,2,4-triazol-3-yl)thio)acetic acid has almost no effect on antiradical activity, except for compound 9 (the antiradical effect is reduse).